Aristotle on Language and Style : The Concept of Lexis - Kotarcic, Ana (Cambridge University Press, 2020)
Cover -- Half-title page -- Title page -- Copyright page -- Dedication -- Contents -- List of Tables -- Preface -- List of Abbreviations and Conventions -- Introduction -- The Lost Treatise on Lexis -- Scholarship on Lexis to Date -- The Aims and Methodology of this Book -- Overview of the Structure of this Book -- Chapter 1 On the Way to Aristotle's Concept of Lexis -- Plato's Conception of Lexis -- Lexis in Isocrates' Works -- Aristotle's Definitions of Lexis -- The Three Levels of Lexis -- Chapter 2 The First Level of Lexis: Aristotle's Fundamentals of Language -- Aristotle's Linguistic Elements -- The Functioning and Function of Language -- Chapter 3 The Second Level of Lexis: Language in Use -- Hellēnizein and barbarizein -- The Attic Standard and the Other Greek Dialects -- Sociolectal Variations within Aristotle's Speech Community -- Chapter 4 The Third Level of Lexis: Its Intra-textual Aspect -- Aretē lexeōs -- Form and Genre -- Chapter 5 The Third Level of Lexis: Its Extra-textual Aspect -- Medium -- Hypokrisis -- Lexis and Audience -- Purpose and Function of Lexis on its Third Level -- Chapter 6 Metaphor Revisited -- Appendix Lexis in Plato's Republic 3.392c7-398b8 -- Bibliography -- Index Locorum -- Index Verborum Graecorum -- Index Generalis.